2005
DOI: 10.5194/nhess-5-741-2005
|View full text |Cite
|
Sign up to set email alerts
|

The 8 and 9 September 2002 flash flood event in France: a model intercomparison

Abstract: Abstract. Within the framework of the European Interreg IIIb Medocc program, the HYDROPTIMET project aims at the optimization of the hydrometeorological forecasting tools in the context of intense precipitation within complex topography. Therefore, some meteorological forecast models and hydrological models were tested on four Mediterranean flash-flood events. One of them occured in France where the South-eastern ridge of the French "Massif Central", the Gard region, experienced a devastating flood on 8 and 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…Moreover, moist convection is an intrinsic source of forecast uncertainty, therefore limiting predictability of heavy precipitation events, even if we assume having a perfect model and a perfectly predictable large scale situation (Hohenegger and Schär, 2007). Therefore, despite the remarkable improvements obtained in the last years, NWP models, even at high horizontal resolution and short forecast times, are usually not yet able to predict timing, spatial location and intensity of precipitation (Anquetin et al, 2005;Richard et al, 2007) with satisfactory accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, moist convection is an intrinsic source of forecast uncertainty, therefore limiting predictability of heavy precipitation events, even if we assume having a perfect model and a perfectly predictable large scale situation (Hohenegger and Schär, 2007). Therefore, despite the remarkable improvements obtained in the last years, NWP models, even at high horizontal resolution and short forecast times, are usually not yet able to predict timing, spatial location and intensity of precipitation (Anquetin et al, 2005;Richard et al, 2007) with satisfactory accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Deidda, 2000;Regimbeau et al, 2007), are needed. Several past studies have assessed the value of convection-permitting meteorological forecasts to drive hydrological models dedicated to Mediterranean flash-floods (Anquetin et al, 2005;Chancibault et al, 2006;Vincendon et al, 2009). These studies found that the precipitation underestimation was significantly less marked for the convection-permitting QPF, but there were still uncertainties on rainfall location, which could be detrimental to good discharge forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondence to: M. Kunz (michael.kunz@imk.uka.de) to predict not only the location and the time of convection initiation (Anquetin et al, 2005;Meißner et al, 2007), but also the type and intensity of thunderstorms. Severe thunderstorms are frequently associated with heavy rainfall, hail, or local storms that are a major cause of natural disasters particularly over mountainous terrain that favor the initiation or the triggering of convection (Orville, 1965;Banta, 1990;Barthlott et al, 2006).…”
Section: Introductionmentioning
confidence: 99%